MAKNA SIMBOLIK TRADISI BAKAYU DAN MANGAMPIANG DI NAGARI BATIPUAH ATEH KECAMATAN BATIPUAH KABUPATEN TANAH DATAR PROVINSI SUMATRA BARAT - Rahmad Fauzi Saputra; Noor Efni Salam (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The tradition of bakayu and mangampiang is one of the traditional cultures of the Minangkabau people that comes from Nagari Batipuah Ateh, Batipuah District, Tanah Datar District. Bakayu and mangampiang is a very rare tradition in Minangkabau. In the tradition of bakayu and mangampiang, there are symbolic aspects that have certain meanings represented by clothing, tools used in the tradition of bakayu and mangampiang. The purpose of this study was to determine the symbolic situation (physical and social aspects) in the tradition of bakayu and mangampiang in Nagari Batipuah Ateh, Batipuah District, Tanah Datar District. To determine the values contained in the tradition bakayu and mangampiang in Nagari Batipuah Ateh, Batipuah subdistrict, Tanah Datar.This study uses a qualitative method with a phenomenological approach and uses the symbolic interaction theory of George H Mead. The informants in this study were the perpetrators of bakayu and mangampiang, traditional leaders, and communities who were selected purposively. Data collection techniques carried out are through observation, interviews, and documentation. To test the validity of the data used source triangulation.The results of this study indicate that symbolic meaning situation tradition bakayu and mangampiang include physical and social aspects. Physical aspects describe the relation of objects / equipment to the activities carried out, while the social aspects include behavior and actions taken by takziah actors. In the tradition bakayu and mangampiang there contained values are religious values and social values. Religious values remind of the close relationship between a servant and his creator, while social values include the value of solidarity, family values, and the value of mutual cooperation.